Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus - Bohn, Horst (Zootaxa, 2019)
An initial contribution to the revision of the genus Dziriblatta Chopard, 1936a, formerly synonymized erroneously with Lobolampra Houlbert, 1927, is presented. The species of the genus, hitherto placed in the subgenera Phyllodromica, Arbiblatta Chopard, 1936a and Lobolampra Houlbbert, 1927, of the genus Phyllodromica Fieber 1853, are distributed on the northern Macaronesian Islands, in southern Spain, North Africa, and the Near East (Israel, Cyprus). The genus is divided into nine new subgenera: Autumnoblatta subgen. nov., Blattantis subgen. nov., Discleroblatta subgen. nov., Dziriblatta subgen. nov., Macaroblatta subgen. nov., Monoscleroblatta subgen. nov., Pauciscleroblatta subgen. nov., Sculptoblatta subgen. nov., and Sulcoblatta subgen. nov.. The characteristics of the genus and its subgenera are described including also a determination key which allows the discrimination of the subgenera in both sexes. The presumable phylogenetic position of the genus and the relationships between the subgenera are discussed and shown in cladograms. The described species and their distribution are shown in numerous figures and distribution maps, respectively.Three new species are described: Dziriblatta (Sculptoblatta) prisca spec. nov., Dziriblatta (Autumnoblatta) nasuta spec. nov., and Dziriblatta (Macaroblatta) dendroglandulosa spec. nov. Nomenclatory changes: The species Blatta carpetana Bolívar, 1873, is designated as lectotype for the subgenus Lobolampra Houlbert, 1927. New synonyms: Aphlebia cazurroi Bolívar, 1885, is a junior synonym of Dziriblatta algerica (Bolívar, 1881); Dziriblatta theryi Chopard, 1936a, Hololampra finoti Bolívar, 1914, and Lobolampra adelungi Chopard, 1943, are synonyms of Dz. (Pauciscleroblatta) kroumiriensis (Adelung, 1914); Dz. vicina Chopard, 1936b, is a synonym of Dz. (Monoscleroblatta) merrakescha (Adelung, 1914).